HUBUNGAN KELINCAHAN DAN KECEPATAN DENGAN KEMAMPUAN MENGGIRING BOLA PADA TIM SEPAKBOLA PEKANBARU CITY SOCCER SCHOOL - FadliRahman Efendi Efendi; Ramadi '; Ardiah Juita Juita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: Problems that encountered in team “PekanbaruCity Soccer School” is a poor ability in dribbling with several weaknesses which makes the result of the match is not satisfied enough. The factors that caused the poor dribbling are less of agility and speed, so the player does not have a good agility and speed in flamming the opponents. This research used correlation research methodology which aimed to analyze how far the variables for one factor is related to another. Correlation is a research design which purposed to determine the relationship level of different variables in a population which aimed to know how much the contribution between independent variable and dependent variable (Arikunto, 2006:131). Population is the whole research object. The population of this research is the whole people in team “PekanbaruCity Soccer School”in the total of 24. To obtain the research data, the writer used dodging run for agility test,sprint 40 yard for speed test and dribbling skill test. The data was analyzed by a simple moment product correlation. Based on the data analysis, correlation koifisien was obtained r hitung=0,622> than r tabel=0,413. So, Ha is accepted while Ho is rejected. It means that there is a relationship between agility and speed towards dribbling ability, where correlation of a variable to another variable is determined from r hitung > r tabel and significance (Sugiyono, 2008:258). Keywords : agility, speed, dribbling, soccer